2010
DOI: 10.1523/jneurosci.0381-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Centrosome Motility Is Essential for Initial Axon Formation in the Neocortex

Abstract: The mechanisms underlying the normal development of neuronal morphology remain a fundamental question in neurobiology. Studies in cultured neurons have suggested that the position of the centrosome and the Golgi may predict the site of axon outgrowth. During neuronal migration in the developing cortex, however, the centrosome and Golgi are oriented toward the cortical plate at a time when axons grow toward the ventricular zone. In the current work, we use in situ live imaging to demonstrate that the centrosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(143 citation statements)
references
References 46 publications
8
135
0
Order By: Relevance
“…17,18 Recently, it has been demonstrated that centrosomal proteins are essential for microtubule organization and centrosome motility that have important roles in axonal formation. 19 ZNF238 is a POZ/zinc finger transcriptional repressor gene. 20 Mice with targeted knock out of ZNF238 display severe hypoplasia of the cerebral cortex and the hippocampus, along with increased apoptosis of progenitors in the ventricular zone.…”
Section: Deletion Of 1q43-q44 Scs Nagamani Et Almentioning
confidence: 99%
“…17,18 Recently, it has been demonstrated that centrosomal proteins are essential for microtubule organization and centrosome motility that have important roles in axonal formation. 19 ZNF238 is a POZ/zinc finger transcriptional repressor gene. 20 Mice with targeted knock out of ZNF238 display severe hypoplasia of the cerebral cortex and the hippocampus, along with increased apoptosis of progenitors in the ventricular zone.…”
Section: Deletion Of 1q43-q44 Scs Nagamani Et Almentioning
confidence: 99%
“…However, conflicting evidence has come from studies of centrosome function in axon development. The centrosome and associated Golgi apparatus predict the site of axon formation in cultured mammalian cerebellar granule and hippocampal neurons (de Anda et al, 2005;Zmuda and Rivas, 1998) and in cortical slices (de Anda et al, 2010). Furthermore, disruption of centrosome function inhibits axon formation in cortical slices (de Anda et al, 2010) and in cultured Drosophila neurons (de Anda et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Centrioles play important roles in controlling the polarity and migration of neuronal cells (de Anda et al 2005;de Anda et al 2010;Ge et al 2010;Lizarraga et al 2010;Kuijpers and Hoogenraad 2011). During evolution of the human brain, the neocortex, which is involved in higher cognitive function, has expanded greatly compared to other mammals (Borrell and Reillo 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear speckles and the nucleolus play basic roles in the metabolism of all cells (Boisvert et al 2007;Spector and Lamond 2011). Cell polarity and cell migration in human neuronal cells, in which centrioles play a key role (de Anda et al 2005;de Anda et al 2010;Ge et al 2010;Lizarraga et al 2010;Kuijpers and Hoogenraad 2011), have facilitated the unique expansion of the neocortex during evolution of the human brain (Taverna et al 2014;Florio et al 2015).…”
Section: Discussionmentioning
confidence: 99%